Espacios virtuales universitarios - Joaquín GARCÍA; Ferrán FERRER; Rafael MOMPÓ; Luis M. NAYA (Ediciones Universidad de Salamanca, 2016)
This article seeks to show that the transformations in educational activities, within the society of knowledge, stem from the introduction of a new medium in communications. This medium, just as in oral cultures, or in reading-writing cultures, provides new spaces for the designing of training activities. If the subject-object contrast entails the corresponding reality-text, the word permits texts on reality the same as writing does. The Information and Communication Technologies (ICT) create renewed textual possibilities in addition to those available in the culture. New integrating spaces are created for training activities. The authors refer specifically to the levels of higher education.